Experimental investigation on material migration phenomena in micro-EDM of reaction-bonded silicon carbide - Liew , Pay Jun; Yan , Jiwang; Kuriyagawa, Tsunemoto (Elsevier, 2013)
Material migration between tool electrode and workpiece material in micro electrical discharge machining of reaction-bonded silicon carbide was experimentally investigated. The microstructural changes of workpiece and tungsten tool electrode were examined using scanning electron microscopy, cross sectional transmission electron microscopy and energy dispersive X-ray under various voltage, capacitance and carbon nanofibre concentration in the dielectric fluid. Results show that tungsten is deposited intensively inside the discharge-induced craters on the RB-SiC surface as amorphous structure forming micro particles, and on flat surface region as a thin interdiffusion layer of poly-crystalline structure. Deposition of carbon element on tool electrode was detected, indicating possible material migration to the tool electrode from workpiece material, carbon nanofibres and dielectric oil. Material deposition rate was found to be strongly affected by workpiece surface roughness, voltage and capacitance of the electrical discharge circuit. Carbon nanofibre addition in the dielectric at a suitable concentration significantly reduced the material deposition rate.